Fideos en casa S.A.C. - Mendiola, Alfredo (2006)
Faced with the imminent entry of the industry leader into the market where Ficasac operates, the management of this company met to analyze and ultimately approve the convenience of expanding the product line. However, during the meeting several alternatives were brought up regarding equipment financing. These alternatives must be assessed in light of two possible future scenarios: taking advantage or not of the tax benefits of the border law. The results of such assessment shall be discussed the following day, for which it is necessary to prepare a report with recommendations on the matter.